2020
DOI: 10.1111/jcpe.13221
|View full text |Cite
|
Sign up to set email alerts
|

The online attention to research in periodontology: An Altmetric study on the most discussed articles on the web

Abstract: Aim: To assess the online attention to research in the field of Periodontology. To assess the correlation between the Altmetric Attention Score (AAS) and the citations count in Web of Science (WOS), Scopus and Dimensions. Material and Methods: The articles were identified by a search performed through the Dimensions Free App. The search included the six journals related to periodontology listed in the Journal Citation Report (JCR) in the year 2017. The 200 articles with the highest AAS were collected and scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 39 publications
5
24
0
Order By: Relevance
“…In Table 3, the published item editorial was included, despite not being considered a study design, because it was able to attract considerable online attention and our aim was to identify every published item able to get a significant AAS. The results are similar to the ones reported in Altmetric studies performed in cardiovascular research, in Neurointervention, Endodontics, and Periodontics [10,23,26,27].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In Table 3, the published item editorial was included, despite not being considered a study design, because it was able to attract considerable online attention and our aim was to identify every published item able to get a significant AAS. The results are similar to the ones reported in Altmetric studies performed in cardiovascular research, in Neurointervention, Endodontics, and Periodontics [10,23,26,27].…”
Section: Discussionsupporting
confidence: 89%
“…In our sample, the correlation between the citation count in the WOS and Scopus with the AAS was poor along the studied period. This result is in agreement with other authors in different fields of dentistry, who observed no correlation between the AAS and the citations count in Scopus or WOS [10,15,19,23]. In the previous investigation in Orthodontics by Livas et al, no correlation was observed between AAS and citation in Scopus (r = 0,09; p = 42), while the correlation in WOS was not assessed by these authors [15].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations